EVALUATION OF THE PILOT PROJECT IMPLEMENTATION IN ENHANCING THE QUALITY OF AGRICULTURAL SELF-SUFFICIENCY DEVELOPMENT AT KARAWANG CLASS IIA CORRECTIONAL INSTITUTION - Faisal, Ilham; Indahdewi, Lauditta (Universitas Nusa Cendana, 2025)
The phenomenon addressed in this study is the suboptimal outcomes of the self-sufficiency development program in the correctional institution, despite the existence of well-designed programs. This research employs a qualitative method with a descriptive approach. Primary data was collected through interviews and direct observations of relevant parties, including inmates, correctional staff, and the head of the work activity division. Data collection techniques included structured interviews and participatory observation. The data analysis used the CIPP (Context, Input, Process, Product) evaluation model, focusing on various aspects such as policy context, resource inputs, implementation processes, and developmental outcomes. The respondents included three inmates involved in the program, correctional staff, and the work activity leader at the Karawang Class IIA Correctional Institution. The results indicate that the agricultural pilot project has been implemented but faces several challenges, such as limited resources, inadequate facilities, and a lack of motivation among the inmates. Keywords: Agriculture; Evaluation; Inmates; Self-Reliance Training